Do fully erupted third molars affect the dental and periodontal health of adjacent second molars? A CBCT-based retrospective study in the Yemeni population - Manal M. Al-Hajri; Abduljabbar M. Al-Sameai (BMC Oral Health)
Abstract Background Periodontal pathologies and caries affecting second molars (M2s) are frequently linked to the presence of adjacent third molars (M3s). This study assessed the association between fully erupted M3s and dental and periodontal/cariogenic conditions in M2s using cone-beam computed tomography (CBCT). Methods A retrospective comparative analysis evaluated 400 CBCT scans from Yemeni patients (≥ 18 years) collected between January 2019 and March 2021. Scans were divided equally into Group I (with fully erupted M3s, n = 200) and Group II (without M3s, n = 200). Outcomes included caries, root canal treatment (RCT), external root resorption (ERR), furcation involvement (FI), lamina dura (LD) integrity, and alveolar bone resorption (ABR) at six anatomical sites around each second molar. Data were analyzed using SPSS version 24, with chi-square test for associations, Mann-Whitney test for mean comparisons, and a multivariable logistic regression model to determine adjusted odds ratios (AORs) and confidence intervals (CIs), considering a p-value < 0.05 as statistically significant. Results Fully erupted M3s significantly increased risks of adjacent M2 pathologies (all p < 0.001). Group I exhibited markedly higher adjusted odds of caries (AOR = 32.53), ERR (AOR = 6.26), FI (AOR = 19.99), RCT (AOR = 9.15), and LD absence (AOR = 10.72) compared to Group II. ABR at all anatomical sites (mesiobuccal, mesiolingual, mid-buccal, mid-lingual, distobuccal, distolingual) was greater in Group I (p < 0.05). Conclusions Fully erupted M3s are strongly associated with periodontal and cariogenic complications in adjacent M2s within the Yemeni population. CBCT proves effective for diagnosing structural periodontal pathologies, underscoring its utility in clinical evaluations.